Distinct Mechanism of Cysteine Oxidation-Dependent Activation and Cold Sensitization of Human Transient Receptor Potential Ankyrin 1 Channel by High and Low Oxaliplatin - Miyake, Takahito; Nakamura, Saki; Meng, Zhao; Hamano, Satoshi; Inoue, Keisuke; Numata, Tomohiro; Takahashi, Nobuaki; Nagayasu, Kazuki; Shirakawa, Hisashi; Mori, Yasuo; Nakagawa, Takayuki; Kaneko, Shuji (Frontiers in Physiology, 2017)
1. Introduction Oxaliplatin (L-OHP), a third-generation platinum-based agent, is frequently used to treat locally advanced and metastatic cancers of the colon or rectum. However, it increases the incidence of chemotherapy-induced peripheral neuropathy (CIPN), often resulting in chemotherapeutic dose delay or treatment discontinuation (Falcone et al., 2007; Miltenburg and Boogerd, 2014). In addition to cumulative and chronic CIPN after multiple chemotherapy cycles, oxaliplatin induces a peculiar acute CIPN, characterized by paresthesia, dysesthesia, or acral numbness, in approximately 90% of patients during or within hours of infusion. Acute CIPN is specific to oxaliplatin and often triggered or exacerbated by cold exposure (Wilson et al., 2002; Miltenburg and Boogerd, 2014; Cavaletti and Marmiroli, 2015). The mechanisms underlying L-OHP-induced chronic CIPN can be explained, at least in part, by neurotoxicity in peripheral sensory neurons due to mitochondrial dysfunction and generation of reactive oxygen species (ROS) (Joseph and Levine, 2009; Di Cesare Mannelli et al., 2012; Azevedo et al. 2013) following accumulation of platinum in the dorsal root ganglia (DRG) (Screnci et al., 2000; Tredici et al., 2001). By contrast, L-OHP-induced acute CIPN is recognized as a channelopathy. A body of evidence suggests that it is caused by alteration of the kinetics of the axonal voltage-gated Na+ channel (Lampert et al., 2012; Sittl et al., 2012; Deuis et al., 2013) and/or activation of transient receptor potential ankyrin 1 (TRPA1) (Nassini et al., 2011; Zhao et al., 2012). TRPA1 is a polymodal cation channel that plays a pivotal role as a nociceptor (Wu et al., 2010; Viana et al., 2016). This channel is opened by a large number of irritant chemicals (Bandell et al., 2004; Jordt et al., 2004). TRPA1 is also activated by oxidative stimuli such as ROS and hyperoxia (Takahashi et al., 2008, 2011). TRPA1 activation evoked by most irritant chemicals and oxidative stimuli is caused by covalent or oxidative modification of cysteine residues in the N-terminal region (Hinman et al., 2006; Macpherson et al., 2007). On the other hand, we previously identified another mechanism for TRPA1 activation; a decrease in oxygen concentration diminishes the activity of prolyl hydroxylases (PHDs) and relieves TRPA1 from